2003
DOI: 10.3998/ark.5550190.0004.104
|View full text |Cite
|
Sign up to set email alerts
|

E/Z Conformational equilibrium of N-substituted 2H-pyran-2-imines

Abstract: Prevailing Z-conformations were found in N-aryl(or alkyl)substituted 2H-pyran-2-imines 4a-e on the NMR time scale. Conformational assignment was based on 1 H and 13 C NMR chemical shifts as well as on induced shifts by LSR. The barrier of E/Z interconversion ( ) was calculated from variable temperature ≠ ∆ Tc G 1 H-NMR spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
3
2
0
Order By: Relevance
“…It is noteworthy that the angle difference Δ exo is smallest for the trans isomer 17c (+1.8 o ) and largest for the cis isomer 17b (+15.0 o ); this closely parallels the analogous structures 10 and 11 (Table 1). In agreement with experimental data [25], the trans isomer 17c is calculated to be the more stable (ΔG rel -0.23 kcal mol -1 ) (Table 5).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…It is noteworthy that the angle difference Δ exo is smallest for the trans isomer 17c (+1.8 o ) and largest for the cis isomer 17b (+15.0 o ); this closely parallels the analogous structures 10 and 11 (Table 1). In agreement with experimental data [25], the trans isomer 17c is calculated to be the more stable (ΔG rel -0.23 kcal mol -1 ) (Table 5).…”
Section: Resultssupporting
confidence: 86%
“…To explore whether similar anomeric effects are found in other heterocyclic rings with exocyclic substituents, we have calculated properties of the pyrone derivatives 17a-d. N,4,6-Triphenypyran-2-imines are known [23,24], and Uncuţa and coworkers, in a detailed NMR study, have shown that in equilibrium mixtures, e.g., 17b,c, the trans (Z) configuration prevails [25].…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the angle difference ∆ exo is smallest for the trans isomer 17c (+1.8 o ) and largest for the cis isomer 17b (+15.0 o ); this closely parallels the analogous structures 10 and 11 (Table 1). In agreement with experimental data [25], the trans isomer 17c is calculated to be the more stable (∆G rel -0.23 kcal mol -1 ) (Table 3).…”
Section: Resultssupporting
confidence: 86%
“…To explore whether similar anomeric effects are found in other heterocyclic rings with exocyclic substituents, we have calculated properties of the pyrone derivatives 17a-d. N,4,6-Triphenypyran-2-imines are known [23,24], and Uncuţa and coworkers, in a detailed NMR study, have shown that in equilibrium mixtures, e.g., 17b,c, the trans (Z) con guration prevails [25]. Table 4 reveals that the structural changes in the series 17a-d are similar to the trends in Tables 1 and 2.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation